2022
DOI: 10.1017/glj.2022.78
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Euro and Energy Considerations: Can the ECB Introduce the Digital Euro Considering the Potential Energy Requirements?

Abstract: The ECB has two mandates its primary and secondary mandate. Its primary mandate has been the focus of many discussions but its secondary mandate is less frequently discussed. Nevertheless this mandate has important objectives and should not be considered obsolete. This article examines the legal status of the secondary mandate of the ECB with regard to climate change. In particular this article will consider the role of the secondary mandate with regard to the Digital Euro and energy targets. The Digital Euro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other articles strictly focus on new money [ 119 , 120 ], CBDCs as new financial instruments [ 121 ], the digital Euro [ 122 ] or various cryptocurrencies and the sustainability-related ecosystem around them [ [123] , [124] , [125] , [126] , [127] ]. By constructing an overview of how modern money is created and combining contemporary heterodox theories and the most recent empirical data, it is suggested that a greater institutional understanding of modern money processes might be useful for enhancing our ability to consider how money generation might more effectively address the needs of the current social and environmental system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other articles strictly focus on new money [ 119 , 120 ], CBDCs as new financial instruments [ 121 ], the digital Euro [ 122 ] or various cryptocurrencies and the sustainability-related ecosystem around them [ [123] , [124] , [125] , [126] , [127] ]. By constructing an overview of how modern money is created and combining contemporary heterodox theories and the most recent empirical data, it is suggested that a greater institutional understanding of modern money processes might be useful for enhancing our ability to consider how money generation might more effectively address the needs of the current social and environmental system.…”
Section: Discussionmentioning
confidence: 99%
“…The ECB's primary objective has been discussed intensively. The secondary objectives include the development of the Digital Euro as well as the energy sustainability of the bank [ 122 ].…”
Section: Discussionmentioning
confidence: 99%